WORKSHOP DAN PENDAMPINGAN PENGEMBANGAN BAHAN AJAR BERBASIS DEEP LEARNING BAGI GURU SEKOLAH DASAR - Rosmiati; Wahyu Susiloningsih; Amelia Widya Hanindita; Bahauddin Azmy; Ismatus Sovia Nadila; Dionisius Ronaldino Fernanandes Dugis; Ronaldino, Ihda Safira (Universitas PGRI Adi Buana Surabaya, 2026)
The transformation of 21st-century learning and the implementation of the Merdeka Curriculum require elementary school teachers to design learning experiences that are oriented toward deep, reflective, and meaningful understanding. However, many teachers still face limitations in developing instructional materials that systematically and contextually integrate Deep Learning principles. This community service program aimed to enhance elementary school teachers’ competencies in developing Deep Learning–based instructional materials through workshops and sustained mentoring. The program was conducted from November to December 2025 and involved 13 elementary school teachers from several public schools inKutorejo District, Mojokerto Regency. reinforcement workshops, mentoring in instructional material development through small- group guidance and individual consultations, as well as formative feedback and iterative revisions. The results indicated improvements in teachers’ understanding and skills in developing Deep Learning–based instructional materials that incorporate clear learning objectives, meaningful learning activities, reflective prompts, and authentic assessments. In addition to producing feasible and classroom-ready instructional materials, the mentoring activities also contributed to increased teachers’ confidence, independence, and pedagogical awareness in designing learning experiences focused on students’ deep understanding. Therefore, this program demonstrates that a workshop model combined with sustained mentoring is effective in strengthening elementary school teachers’ capacity as innovative and sustainable designers of Deep Learning–based instruction.